2005
DOI: 10.1093/heapol/czi034
|View full text |Cite
|
Sign up to set email alerts
|

Implementing global knowledge in local practice: a WHO lung health initiative in Nepal

Abstract: Clinical practice guidelines are used widely to improve the quality of primary health care in different health systems, including those of low-income countries. Often developed at international level and adapted to national contexts to increase the feasibility of effective uptake, guideline initiatives aim to transfer global scientific knowledge into local practice. The WHO's Practical Approach to Lung Health (PAL) is an example of such an initiative and is currently being developed to improve the quality of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…2005). In Nepal, the Ministry of Health (MoH) introduced the generic PAL guidelines in one district, adapting them to national circumstances (Asbroek et al. 2005), and training primary healthcare workers from selected pilot health facilities in them.…”
Section: Introductionmentioning
confidence: 99%
“…2005). In Nepal, the Ministry of Health (MoH) introduced the generic PAL guidelines in one district, adapting them to national circumstances (Asbroek et al. 2005), and training primary healthcare workers from selected pilot health facilities in them.…”
Section: Introductionmentioning
confidence: 99%
“…The simplicity of the Boolean operator framework means that elements can be rewritten to reflect the perspectives of appraisers, and their particular stakeholder groups, and to allow for the characteristics peculiar to the set of guidelines being analysed. For example, guidelines written for less developed countries may have extensive generic background material that would not normally score well on AGREE, but which is necessary for less skilled health workers [35]. The Boolean‐based User Guide can be rewritten so that scorers can accommodate this.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of PAL feasibility in rural Nepalese areas showed that to improve implementation, the national guidelines should be better and the implementation strategy upgraded [44]. It is vital to keep health centre staff engaged and aware of the value of the study.…”
Section: Difficulties During Pal Implementationmentioning
confidence: 99%
“…The integration of guidelines requires intensive collaboration, bringing together key personnel from multiple Ministry of Health Units and vertical disease programmes [45]. It is necessary to develop additional interventions that tackle culture-specific and health system-specific barriers [44].…”
Section: Difficulties During Pal Implementationmentioning
confidence: 99%